Health-related quality of life among multimorbid patients using the EQ-5D-5L value set for India - Sahoo, Krushna Chandra; Sinha, Abhinav; Dash, Girish Chandra; Sahoo, Rakesh Kumar; Bhattacharya, Debdutta; Dash, Purna Chandra; Mohanty, Lalatendu; Mahapatra, Pranab; Rajsekhar, Kavitha; Pati, Sanghamitra (Frontiers in Public Health, 2025)
Multimorbidity presents major challenges to healthcare systems worldwide. Assessing health-related quality-of-life (HRQoL) in multimorbid patients is essential for understanding the overall impact of the patient’s health conditions on wellbeing and the complexities of patient management. This study assessed the HRQoL of multimorbid patients in India using the EQ-5D-5L value set. This observational study included 906 patients from tertiary healthcare facilities in Odisha, India, and used consecutive time-based sampling methods, conducted from January to April 2023. The study examined the relationship between HRQoL measures and utility scores using ordinary least squares regression and multiple regression analysis. The results showed that mean utility scores decreased as the number of health conditions increased, with scores of 0.677 for one condition, 0.577 for two conditions, 0.354 for three conditions, and 0.098 for four or more conditions. Combining stroke/paralysis with other health issues resulted in negative utility ratings. The findings showed that younger age (p = 0.003), urban residence (p = 0.027), higher education (p = 0.018), being married (p = 0.006), engaging in physical activity (p = 0.001), and having fewer health conditions were independently associated with higher utility scores. The study highlights the correlation between multimorbidity and HRQoL in older adults, highlighting implications for healthcare systems and clinical and policy decisions for multimorbid patients.